Peluang Desa Lumbung Pangan dalam Meningkatkan Ketahanan Pangan Rumah Tangga Tani - Anisya, Ayu Putri Merry; Waluyati, Lestari Rahayu (Universitas Muhammadiyah Yogyakarta, 2019)
Food security has three subsystems namely food availability, food access and food utilization. To reduce poverty and to improve food security, Yogyakarta City implements food barn program. This research was conducted in food barns village and non food barns villages in Seyegan District. Samples were taken, namely the household of farmers as much as 100 respondents. Sampling was done by a random sampling method. Using cross classification analysis between food expenditure share (PPP) and energy adequacy rate (AKE) to determine the level of food security and using the method of Logit Ordered Model to see the influence of the status of food barns against food security opportunities for farm households. The result showed that food barns in foodresistant state was 58%, vulnerable to food was 8%, less food 9% and foodprone to 4%, while non food barns villages showed food-resistant state 56%, food vulnerable 5%, less food 6 % and food prone 11%. Food security opportunities for food-resistant farmers in food barns village are higher than the village of food barns. The results of the analysis using ordinal logit method showed that the price of tempe and tofu, household income, the number of household members and dummy village status, affects the opportunity of food security farmers ' households.